Determinants of Takaful Patronage Among Entrepreneurs in Sabon Gari Market, Kano State, Nigeria - sulaiman, Sagir muhammad; Dandago, Abba Abdulhamid; Muhammad, Muhammad Abdulaziz; Sabiu, Tasiu Tijjani (Journal of Accounting Research, Organization and Economics, 2020)
Objective This paper examined the determinants of Takaful patronage among the entrepreneurs in Sabon Gari market of Kano metropolis, Nigeria.Design/methodology The paper adopted survey research approach through the use of questionnaire. Respondents were selected using a purposive sampling technique. Multivariate regression was adopted to test the hypothesized model of the study using variance-based SEM. The data was analyzed using Smart-PLS 3.Results The results show that religiosity, trust and confidence and awareness most often positive and are found to significantly influence patronage of Takaful services at significant level of 0.05 while the three explanatory variables were able to explain 58% variation in the dependent variable.